Genetic associations with C‐reactive protein level and white blood cell count in the KARE study. (13th July 2012) - Kong, M.; Lee, C.
Summary C‐reactive protein (CRP) and white blood cell (WBC) have been utilized as critical markers contributing to acute and chronic inflammation. Genome‐wide associations were examined to identify nucleotide sequence variants associated with the two markers using 8842 individuals in the Korean Association REsource (KARE) study. A total of six and three nucleotide variants turned out to be associated with CRP and WBC (P < 1.42 × 10−7), and they were mutually exclusive. The only common variant associated with CRP was rs2393791 within hepatocyte nuclear factor 1 alpha (HNF1A) gene [minor allele frequency (MAF) = 0.478]. The only common variant associated with WBC [MAF = 0.468] was rs8078723, an intergenic single nucleotide polymorphism located between proteasome 26S subunits non‐ATPase 3 (PSMD3) and colony‐stimulating factor 3 (CSF3) in chromosome 17. The 2 variants were also associated with other inflammation‐related phenotypes (P < 0.05), and each phenotype was associated with the variant rs2393791 or with the variant rs8078723. We suggested that HNF1A gene was associated with CRP, and the region including PSMD3 and CSF3 genes was associated with WBC. The two inflammatory markers appeared to have distinct genetic components. Not only the functions of these two markers but also the functions of the corresponding genetic components might be largely complementary in determining inflammation process.